The optimal route search in Bengaluru city transport using Hamilton circuit algorithm - Parkavi S; Parthiban A (Heliyon, 2025)
Traffic congestion is a common transportation issue all over the globe, especially in India's large cities. One of the primary causes of traffic congestion is the sheer volume of private vehicles that travel on city streets and the extensive use of public transportation. The lack of additional road capacity also makes it worse. As a result, many urban road traffic situations, particularly in Bengaluru city in India, are approaching saturation, characterized as the situation where the number of cars using a road is equal to its capacity (V/C=1). One strategy to address the issue of congestion is traffic engineering. So, drawing inspiration and motivation from the outstanding work of Mungporn, Pongsiri et al., “Modeling and control of multiphase interleaved fuel-cell boost converter based on Hamiltonian control theory for transportation applications, IEEE Transactions on Transportation Electrification 6.2, 2020, pp. 519-529”, in this paper, we study an intelligent agent model to perform route engineering for public transportation in the Bengaluru city, based on the Hamilton circuit algorithm and analyze the best and optimal route among the three significant routes out of twelve available using various parameters. The public transit route is changed from being a single path connecting the outgoing and returning routes to a circular route. The results of the simulation indicate that the reconfigured circular routes, optimized using the backtracking algorithm, led to a notable reduction in the traffic load on public transportation. This optimization improves overall traffic flow and alleviates congestion in key areas of Bengaluru.